Drug release study from flexible and rigid drug carrier systems under inhomogeneous pulsed magnetic fields with applications in the molecular transport into cells - Acharya, Basanta (Kansas State University, 2022)
This thesis focuses on the development of drug carrier systems in conjunction with an inhomogeneous pulsed magnetic field to achieve a short time release over the maximum release, in presence of magnetic nanoparticles (MNPs) as triggering agents. This thesis discusses the synthesis of both flexible (magneto-liposomal) and rigid (rattle cages of core Fe₃O₄@SiO₂ shell) drug carrier systems with their characterization, model drug encapsulation, and release assay under inhomogeneous pulsed magnetic field(s). Though the magneto-liposomal formulation with encapsulation of nanoparticles (NPs) at the core, at the bilayer, or the surface of liposomes is not new, the approach here is different from other works regarding the time in which the content is released. In the first project, the magnetic iron oxide nanoparticles are attached to the exterior surface of liposomes through two modifications, first, the coating of iron oxide nanoparticles with gold, and second, the surface modification of liposomes with CHOL-PEG-SH linker so that gold-coated MNPs are attached to a liposomal membrane with gold-thiol interaction. The release of carboxyfluorescein from this magneto-liposomes formulation under the application of magnetic pulses is studied. Further, the role of different types of nanoparticles on the phase transition temperature of liposomes and the effect of osmosis in model drug release from liposomes are explored. In another project, carboxyfluorescein release from magnetoliposomes with MNPs encapsulated at the aqueous lumen or, the lipid bilayer of liposomes is again investigated with applications of short magnetic pulses generated from both higher and lower inhomogeneous magnetic fields. To look further into the pulsatile release rate of the model drug, release after application of each magnetic pulse is measured. This will add a step towards our aim of the fast release kinetics of payload from magneto-liposomal systems. In addition, the release study from magnetoliposomes at different positions of magnets in both Helmholtz and anti-Helmholtz coils is explored which strongly establishes the proof of concept for the use of the pulsed magnetic field system we developed. Besides, the release from rigid drug carrier system is discussed where rattle type mesoporous silica shell structures are used. The release of doxorubicin from these carriers with different core sizes, shell thickness, and effective volumes is investigated. Finally, the use of the inhomogeneous pulsed magnetic field in the transportation of small molecules into the cancerous cells through the formation of micropores within those cells in presence of magnetic nanoparticles is explored. This pilot study investigated the individual and combinational effect of Dextran coated iron oxide NPs, doxorubicin, and magnetic pulses on cellular viability. Moreover, the enhancement of doxorubicin uptake and accumulation along with its effectiveness in this combinational strategy is discussed. It is expected that the use of pulsed magnetic field mediated ultrasound generation from magnetic nanoparticles will have a significant role in biological applications including targeted drug delivery.
Keywords: Magneto-liposomes; Drug release; Rattle-type silica shells; Molecular transport; Pulsed magnetic field